Alliance members' roles in collective field-building: an assessment of leadership and championship within the Population Health Intervention Research Initiative for Canada - Erica Di Ruggiero; Natalie Kishchuk; Sarah Viehbeck; Nancy Edwards; Kerry Robinson; Barbara Riley; Heather Smith Fowler (BMC, 2017)
Abstract Background The Population Health Intervention Research Initiative for Canada (PHIRIC) is a multi-stakeholder alliance founded in 2006 to advance population health intervention research (PHIR). PHIRIC aimed to strengthen Canada's capacity to conduct and use such research to inform policy and practice to improve the public's health by building PHIR as a field of research. In 2014, an evaluative study of PHIRIC at organisational and system levels was conducted, guided by a field-building and collaborative action perspective. Methods The study involved 17 qualitative key informant interviews with 21 current and former PHIRIC Planning Committee and Working Group members. The interviews examined how individuals and organisations were acting as champions and exerting leadership in building the field of PHIR. Results Founding PHIRIC organisational members have been championing PHIR at organisational and system levels. While the PHIR field has progressed in terms of enhanced funding, legitimacy, profile and capacity, some members and organisations faced constraints and challenges acting as leaders and champions in their respective environments. Expectations about the future of PHIRIC and field-building of PHIR were mixed, where longer-term and founding members of PHIRIC expressed more optimism than recent members. All agreed on the need for incorporating perspectives of decision-makers into PHIR directions and initiatives. Conclusions The findings contribute to understanding alliance members' roles in leadership and championship for field-building more generally, and for population health and PHIR specifically. Building this field requires multi-level efforts, collaborative action and distributed leadership to create the necessary conditions for PHIRIC members to both benefit from and contribute to advancing PHIR as a field. Lessons from this 'made in Canada' model may be of interest to other countries regarding the structures needed for PHIR field-building.